A high-throughput dye-reducing photometric assay for evaluating microbial exoelectrogenic ability. (October 2017) - Xiao, Xiang; Liu, Qiu-Yue; Li, Ting-Ting; Zhang, Feng; Li, Wen-Wei; Zhou, Xiang-Tong; Xu, Mei-Ying; Li, Qian; Yu, Han-Qing
Graphical abstract: Highlights: A photometric assay for probing microbial exoelectrogenic ability was developed. This assay could identify the exoelectrogenic abilities of various bacteria. The assay is simple, high-throughput, and reliable. Abstract: Exoelectrogenic bacteria (EEB) can transfer electrons to extracellular electron acceptors and have wide applications in environmental bioremediation and bioenergy generation. Thus, methods for effectively probing the exoelectrogenic ability of EEB are highly desirable. In this work, a simple but efficient photometric assay based on the extracellular reduction of high polar dyes was developed to evaluate the microbial exoelectrogenic ability. Methyl orange were proven to be used as a probe for evaluating the exoelectrogenic ability of EEB. Through monitoring the extracellular dye decolorization under anaerobic conditions, this plate-based photometric assay could rapidly measure the exoelectrogenic ability of various EEB. This approach was also able to evaluate the exoelectrogenic capacity of Shewanella oneidensis MR-1 wild-type strain and its Mtr mutants. Furthermore, the exoelectrogenic ability of mixed cultures in microbial fuel cells was correlated with the extracellular dye decolorization. Thus, this work is useful for the practical implementation of microbial exoelectrogenic ability evaluation.